Galaxy Zoo: bar lengths in local disc galaxies - Hoyle, B; Masters, K; Nichol, R; Edmondson, E; Smith, A; Lintott, C; Scranton, R; Bamford, S; Schawinski, K; Thomas, D (2011)
We present an analysis of bar length measurements of 3150 local galaxies in a volume-limited sample of low-redshift (z < 0.06) disc galaxies. Barred galaxies were initially selected from the Galaxy Zoo 2 project, and the lengths and widths of the bars were manually drawn by members of the Galaxy Zoo community using a Google Maps interface. Bars were measured independently by different observers, multiple times per galaxy (≥3), and we find that observers were able to reproduce their own bar lengths to 3 per cent and each others' to better than 20 per cent. We find a colour bimodality in our disc galaxy population with bar length, i.e. longer bars inhabit redder disc galaxies and the bars themselves are redder, and that the bluest galaxies host the smallest galactic bars (<5h-1kpc). We also find that bar and disc colours are clearly correlated, and for galaxies with small bars, the disc is, on average, redder than the bar colours, while for longer bars the bar then itself is redder, on average, than the disc. We further find that galaxies with a prominent bulge are more likely to host longer bars than those without bulges. We categorize our galaxy populations by how the bar and/or ring are connected to the spiral arms. We find that galaxies whose bars are directly connected to the spiral arms are preferentially bluer and that these galaxies host typically shorter bars. Within the scatter, we find that stronger bars are found in galaxies which host a ring (and only a ring). The bar length and width measurements used herein are made publicly available for others to use. © 2011 The Authors Monthly Notices of the Royal Astronomical Society © 2011 RAS.